Farmer and Field Survey in Cassava-Growing Districts of Rwanda Reveals Key Factors Associated With Cassava Brown Streak Disease Incidence and Cassava Productivity - Nyirakanani, Chantal; Bizimana, Jean Pierre; Kwibuka, Yves; Nduwumuremyi, Athanase; Bigirimana, Vincent de Paul; Bucagu, Charles; Lassois, Ludivine; Malice, Eléonore; Gengler, Nicolas; Massart, Sébastien; Bragard, Claude; Habtu, Michael; et al. (Frontiers in Sustainable Food Systems, 2021)
Cassava (Manihot esculenta Crantz) is a vital crop in Rwanda where it ranks as the third most consumed staple. However, cassava productivity remains below its yield potential due to several constraints, including important viral diseases, such as cassava brown streak disease (CBSD). Because various factors can be addressed to mitigate the impact of viral diseases, it is essential to identify routes of virus contamination in the cassava agrosystems from the seed system to farmer's practices and knowledge. The present study aimed at (1) assessing the current cassava seed system and farmers' practices and their knowledge of the biotic constraints to cassava production, (2) determining the status of CBSD as well as critical factors associated with its spread through the seed system channels, and (3) determining factors that influence cassava productivity in Rwanda. A cross-sectional study was carried out from May to September 2019 in 13 districts of Rwanda. A total of 130 farmers and cassava fields were visited, and the incidence and severity of CBSD were evaluated. CBSD was detected in all cassava-producing districts. The highest field incidence of CBSD was recorded in the Nyanza district (62%; 95% CI = 56–67%) followed by the Bugesera district (60%; 95% CI = 54–65%), which recorded the highest severity score of 3.0 ± 0.6. RT-PCR revealed the presence of CBSD at the rate of 35.3%. Ugandan cassava brown streak virus was predominant (21.5%) although cassava brown streak virus was 4% and mixed infection was 10%. An informal cassava seed system was dominant among individual farmers, whereas most cooperatives used quality seeds. Cassava production was found to be significantly influenced by the use of fertilizer, size of the land, farming system, cassava viral disease, and type of cassava varieties grown (p < 0.001). Disease management measures were practiced by a half of participants only. Factors found to be significantly associated with CBSD infection (p < 0.05) were the source of cuttings, proximity to borders, age of cassava, and knowledge of CBSD transmission and management.